The Influence of Motivation, Discipline, and Academic Achievement on the Entrepreneurial Intentions of Management Students - Isnawan, Mohammad Bagus; Sugiono, Sugiono; Raharjo, Itot Bian (Asa Jurnal Penelitian Pendidikan dan Pembelajaran, 2025)
This research examines the influence of motivation, discipline, and academic achievement on the entrepreneurial intentions of students in the Management Study Program at Universitas Nusantara PGRI Kediri. Utilizing a quantitative approach with a causal-comparative design, data were gathered from 130 final-year students selected through purposive sampling. Data collection involved distributing Likert-scale questionnaires online via Google Forms, ensuring accessibility and efficiency. The analysis employed multiple linear regression using SPSS version 26, preceded by validity, reliability, and classical assumption tests (normality, multicollinearity, and heteroscedasticity). The results indicate that motivation (t=1.981, Sig.=0.000), discipline (t=2.384, Sig.=0.000), and achievement (t=2.178, Sig.=0.001) each have a significant positive effect on entrepreneurial intention. Collectively, these variables account for 62.2% of the variation in entrepreneurial intention (R²=0.622, F=3.384, Sig.=0.001). These findings highlight the pivotal role of motivation, discipline, and achievement in fostering entrepreneurial interest among students, providing valuable insights for higher education institutions to develop targeted entrepreneurship programs that enhance these attributes to prepare students as innovative and competent entrepreneurs.